The Sum of Fears in Cancer Patients Inside the Context of the COVID-19 - Bandinelli, Lucas; Ornell, Felipe; von Diemen, Lisia; Kessler, Felix Henrique Paim (Frontiers in Psychiatry, 2021)
The pandemic resulting from COVID-19 has led to the collapse of the health system in dozens of countries. Parallel to clinical risk, the appearance or intensification of psychiatric symptoms has also been documented. The identification of risk groups is fundamental for the establishment of preventive and therapeutic strategies. Cancer patients appear to be especially vulnerable both from a clinical and psychiatric point of view. Problems related to specific contamination and to the cancer treatments themselves are intertwined, causing a sum of patients' fears to arise, which can cause mental and physical effects. This article aims to analyze this issue and indicate possible tools for patients to deal with issues associated with COVID-19.